Heat‐killed Lactobacillus reuteri and cell‐free culture supernatant have similar effects to viable probiotics during interaction with Porphyromonas gingivalis. (6th November 2019) - Geraldo, Barbara M. C.; Batalha, Marianna N.; Milhan, Noala V. M.; Rossoni, Rodnei D.; Scorzoni, Liliana; Anbinder, Ana Lia
Abstract: Background and objective: In the last decade, numerous studies have been published to clarify the role of probiotics, especially Lactobacillus reuteri, as an adjunct to conventional periodontal treatment. Although the health benefits of probiotics are numerous, they are live bacteria, and the administration of live organisms is not risk‐free. We evaluated the antimicrobial effect of L reuteri and its cell‐free culture supernatant on Porphyromonas gingivalis, a keystone periodontal pathogen, in vitro. We also evaluated the influence of this probiotic in its live, heat‐killed (HKL, paraprobiotic) form and its supernatant on the Galleria mellonella invertebrate model after infection by P gingivalis. Methods: The interaction assay was conducted with P gingivalis and L reuteri preparations (live cells and supernatant preparation). For this, P gingivalis and L reuteri preparations were added to tubes containing Brain Heart Infusion broth and incubated for 3 days. The suspensions were then seeded onto appropriate culture media for the calculation of colony‐forming units per mL (CFU/mL). An in vivo assay with the G mellonella model was also performed. Live L reuteri, HKL, or supernatant was inoculated 2 hours prior to infection with P gingivalis . Survival was evaluated over 7 days, and the number of hemocytes in the hemolymph was estimated 3 hours after P gingivalis infection. Data were then subjected to statistical testing ( α  = 5%). Results: Both live L reuteri and its supernatant had antimicrobial activity against P gingivalis (CFU reduction up to 86%, P  < .05). Moreover, treatment with live and HKL had similar effects on G mellonella survival (increased survival up to 46%, P  < .05). However, only live L reuteri was able to significantly increase the hemocyte density in this invertebrate model. Conclusion: Lactobacillus reuteri antimicrobial activity against P gingivalis and its effects on G mellonella survival after infection with a periodontopathogen do not depend on cell viability. This allows the development of products without live bacterium while maintaining similar effects.